PENGARUH BID ASK SPREAD, VARIANS RETURN, VOLUME PERDAGANGAN , DAN HARGA SAHAM TERHADAP HOLDING PERIOD SAHAM - Ida Subaida (CERMIN: Jurnal Penelitian, 2019)
The capital market or stock market is a container to bring together sellers and buyers of financial instruments with investment objectives. The existence of the capital market provides a role for various parties such as companies, investors, and even for the national economy. The correct information about the company's shares in the stock market is needed by investors as a decision to buy and sell shares and also for the decision to hold or release ownership of financial assets. The purpose of this study is to analyze and provide empirical evidence about the effect of bid ask spread, return variance, trading volume, and stock price on the holding period of shares in companies listed on the Indonesia Indonesia Stock Exchange which are categorized as LQ45 companies. The research sample was 45 samples in the form of companies listed on the Indonesia Indonesia Stock Exchange which included the LQ45 company category in 2017. Hypothesis testing was done by path analysis using SPSS version 22. The results of the study were bid ask spread, variance return, trading volume, and stock price does not affect the holding period.